Dr. Gerald O'Daniel — Deep Plane Facelift — Louisville - O'Daniel, Gerald (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Gerald O'Daniel, practicing in Louisville, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003242; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; louisville